A coordination mechanism to replicate large-scale multi-agent systems - Ductor, Sylvain; Guessoum, Zahia (2018 IEEE ACM 13th International Symposium on Software Engineering for Adaptive and Self Managing Systems (SEAMS), 2018)
Distributed cooperative applications are now increasingly designed as Multi-Agent Systems (MAS). Such applications may be open, dynamic, large scale and exhibit heterogeneous and dynamic agents criticalities. These characteristics create new challenges to the traditional approaches of fault-tolerance. We focus on replication-based preventive approach. The aim is to dynamically and automatically adapt the agent replication strategy (number of replicas and their location), in order to maximize the MAS reliability (guarantee of continuity of computation w.r.t the agents criticalities). In this paper, we describe a decentralized coordination mechanism supporting adaptive replication. In order to provide a clear understanding of the specifics of our proposal, we provide a theoretical validation and report on experimental validations by confronting our proposal with an existing solution that is structurally similar.